Robert Louis Stevenson - Raleigh, Walter Alexander, Sir, 1861-1922 (Salt Lake City, UT : Project Gutenberg, 1995)
"Robert Louis Stevenson" by Sir Walter Alexander Raleigh is a biographical essay written in the early 20th century. This examination highlights the life and works of Robert Louis Stevenson, a prominent author renowned for his imaginative storytelling and literary mastery. The book serves as both a tribute and analysis of Stevenson$1 (Bs contributions to literature, emphasizing his unique talent and enduring legacy. In this insightful piece, Raleigh delves into Stevenson's life, discussing his health struggles while celebrating his literary genius and prolific output. He reflects on Stevenson's ability to blend romance with meticulous style, showcasing his works like "Treasure Island" and "Dr. Jekyll and Mr. Hyde" as central to his acclaim. Raleigh emphasizes Stevenson's zest for life, creativity, and ability to evoke emotions through rich language, while also considering the impact of his early death on the literary world. The essay reveals both the man behind the pen and the rich tapestry of thoughts and themes woven into his body of work, reinforcing Stevenson$1 (Bs place in literary history. (This is an automatically generated summary.)s
Release date is 1995-09-01
Transcribed from the 1906 Edward Arnold edition by David Price
Keywords: Stevenson, Robert Louis, 1850-1894; Authors, Scottish -- 19th century -- Biography